2021
DOI: 10.3126/jpahs.v8i2.31432
|View full text |Cite
|
Sign up to set email alerts
|

Perception of nursing students towards online learning during COVID-19 pandemic

Abstract: Introduction: During COVID-19 pandemic, many academic institutions in Nepal and the world turned to online learning. The present study aimed to explore nursing students’ perception towards online learning.  Method: A cross-sectional analytical study was conducted to identify the perception of nursing students towards online learning in School of Nursing and Midwifery, Patan Academy of Health Sciences (PAHS), Lalitpur, Nepal during October 2020. A total enumerative sampling technique was used to collect d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
5
1
1
Order By: Relevance
“…This result is consistent with the findings of other authors (Mohamed Abd El-Hamed Diab & Fouad Elgahsh, 2020;Olum et al, 2020), who also found that technical equipment and support are important in influencing studentsʼ attitudes towards online teaching. Despite previous claims by some authors that quality of Internet connection also influences studentsʼ attitudes towards online teaching (Achmad et al, 2021;Khagi et al, 2021;Mukasa et al, 2021;Olum et al, 2020), the data collected in this study did not yield such a result. No difference was found between the students in terms of the quality and speed of the Internet connection they had while observing online classes.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is consistent with the findings of other authors (Mohamed Abd El-Hamed Diab & Fouad Elgahsh, 2020;Olum et al, 2020), who also found that technical equipment and support are important in influencing studentsʼ attitudes towards online teaching. Despite previous claims by some authors that quality of Internet connection also influences studentsʼ attitudes towards online teaching (Achmad et al, 2021;Khagi et al, 2021;Mukasa et al, 2021;Olum et al, 2020), the data collected in this study did not yield such a result. No difference was found between the students in terms of the quality and speed of the Internet connection they had while observing online classes.…”
Section: Discussioncontrasting
confidence: 99%
“…This study revealed that 50.51% of respondents had their own laptop. This result agrees with other similar studies [12,14].…”
Section: Discussionsupporting
confidence: 94%
“…Finding showed that 52.55% respondents had favorable perception towards online learning which is consistent with a study done in Palpa, Nepal revealed that 56.9% of the respondents had positive perception towards online learning [13]. Finding was also similar with another study done by Patan Academy of Health Sciences (PAHS), School of Nursing and Midwifery, it was found that 53.4% of the nursing students had favorable perceptions [12]. There was contrary to the finding of this study conducted in Nepal in Nepalese Army Institute of Health Sciences among 513 students during the COVID-19 pandemic showed 77% students had a positive perception of online learning [15].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings were supported by recent research carried out by Rana Khagi, et al, (2021) who claimed that access to the internet, the requirement for using mobile phone data, and academic level were all strongly correlated with the student's perception. Similarly, the finding of a study done by Kusum Lata and Surat Ram Kudi.…”
Section: Itemssupporting
confidence: 79%